Managing the IVF laboratory during a pandemic: international perspectives from laboratory managers - Hickman, Cristina (Reprod Biomed Online, 2020)
Fertility societies worldwide responded to the COVID-19 pandemic by recommending that fertility clinics close, or sharply reduce, the clinical operation, leading to a shift in the management of IVF laboratories in three phases: shutdown preparation; maintenance during shutdown; and restart. Each of these phases carries distinct risks that need identification and mitigation, forcing laboratory managers to rethink and adapt their procedures in response to the pandemic. The sudden and unprecedented nature of the pandemic forced laboratory managers from around the world to base decisions on opinion and experience when evidence-based response options were unavailable. These perspectives on pandemic response were presented during a virtual international symposium on COVID-19, held on 3 April 2020, and organized by the London Laboratory Managers’ Group. Laboratory managers from seven different countries at different stages of the pandemic (China, Italy, Spain, France, UK, Brazil and Australia) presented their personal experiences to a select audience of experienced laboratory managers from 19 different countries. The intention of this paper is to collect the learnings and considerations from this group of laboratory managers who collaborated to share personal experiences to contribute to the debate surrounding what constitutes good IVF laboratory practice in extraordinary circumstances, such as the COVID-19 pandemic.